Psychoanalytic Study on Kevin's Character in We Need to Talk About Kevin Movie - Alifia Sifriliani; Euis Kurniasih (PIKTORIAL : Journal of Humanities, 2022)
The aim of the research is to analyze the characterization of the main characters Kevin in the We Need to Talk about Kevin film by Lynne Ramsay based on Sigmund Freud's Psychoanalysis theory about the three psychological elements possessed by humans, namely the id, ego, and superego. Library research method is used to write this thesis. In addition, the author also used content analysis research techniques to analyze the data. After the author conducted research on the We Need to Talk about Kevin film by Lynne Ramsay, the author concluded that Kevin have all the psychological elements of the id, ego, and superego. The overall data on Kevin's character obtained by the author are 6 data. There are 3 data elements of id (50%), followed by 2 data of ego elements (33,3%), and 1 data of superego elements (16.7%). Therefore, it can be concluded that id is the most dominant psychological element in Kevin's character